Report on Improved Agricultural Implements in Maharashtra State - Planning Commission (Planning Commission, 1965)
Geographical position : The State of Maharashtra, with an area of 3,07,906 square kilo-metres, lies below the Tropic of Cancer, between the northern latitudes of 16.4 and 22.1 degrees and eastern longitudes of 72.6 and 80.9 degrees. The State is, thus, situated entirely in the tropical region but due to higher altitude and proximity to the Arabian sea, its western parts have some-what milder summer than that of the eastern parts.
Agriculture Team Committee on Plan Projects
Agriculture Team Committee on Plan Projects